Literature review of the fossil record of Systellognatha (Insecta: Plecoptera) and its implications for the biogeography of the Order - Kirkaldy, Abigail P.; Barber-James, Helen M.; Richoux, Nicole B.; Villet, Martin H. (Zootaxa, 2025)
The unusual anti-tropical distribution of the Plecopteran (Insecta, stoneflies) suborders Antarctoperlaria and Arctoperlaria, and the biogeographical processes that caused it have fascinated researchers for decades. In particular, debate surrounds what led to the initial diversification of each sub-order, and the dispersal of two Arctoperlarian families, Notonemouridae and Perlidae, into the Southern Hemisphere. The fossil record of Plecoptera is vital for exploring these questions, as it provides the only direct evidence of ancient Plecopteran diversity and occurrence, and can be used to constrain phylogenetic studies. However, many authors question the stonefly fossil record, citing uncertain and contradictory taxonomy caused by an overreliance on phenetic similarity instead of syn- and autapomorphies. Here, we review the published descriptions and figures of all fossilised Systellognatha and fossilised austral species to assess the presence of apomorphic characters, and critically examine their placement in the Plecopteran phylogeny. As the monophyly and diagnoses of extinct families and genera are not assessed, formal systematic reclassifications are not proposed, and this work is explicitly disclaimed as a nomenclatural revision in terms of Article 8.2 of the International Code of Zoological Nomenclature. We found insufficient evidence to support the current classification of 56% of the 113 fossil species reviewed. From the remaining species, specimens with apomorphies of Gripopterygidae, Notonemouridae, Peltoperlidae, Pteronarcyidae, Perlidae and Perlodidae were identified. These allowed for the recommendation of 12 fossil species for the calibration of dated phylogenetic analyses and palaeobiogeographical interpretations. These fossils point to Antarctoperlaria and Arctoperlaria diverging due to vicariance, either on Pangea or shortly following its separation in the Jurassic. Notonemouridae probably dispersed into the Southern Hemisphere during the Early Jurassic, with two independent dispersals of Perlidae occurring in the Cenozoic.